2015
DOI: 10.1007/s12288-015-0578-2
|View full text |Cite
|
Sign up to set email alerts
|

Is JAK2V617F Mutation the Only Factor for Thrombosis in Philadelphia-Negative Chronic Myeloproliferative Neoplasms?

Abstract: The most common genetic disorder in Philadelphia negative chronic myeloproliferative neoplasms is the JAK2-V617F mutation. In the present study, we aimed to determine risk factors for thrombosis in patients with essential thrombocytosis and polycythemia vera. We screened the medical records of 101 patients. Risk factors which may predict thrombosis were recorded. Venous thrombosis (VT) before diagnosis was significantly higher in JAK2 positive patients. VT after diagnosis was similar in JAK2 positive and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Although the current Turkish study [1] had a relatively small sample size, it revealed some unusual findings. The JAK2 mutation's presence modulated thrombotic risk prior to diagnosis, but not subsequently, suggesting a neutralization of its effect by effective therapy.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Although the current Turkish study [1] had a relatively small sample size, it revealed some unusual findings. The JAK2 mutation's presence modulated thrombotic risk prior to diagnosis, but not subsequently, suggesting a neutralization of its effect by effective therapy.…”
mentioning
confidence: 67%
“…The JAK2 mutation, if present, is a well-established risk factor for thrombosis in ET [3,4], a finding has also confirmed in the publication by Uyanik et al [1]. The V617F allele burden is known to be associated with acquired activated protein C resistance, low free PS and increased levels of soluble markers of endothelial and platelet activation including elevated tissue factor [5][6][7].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies have shown that JAK2V617F may increase the likelihood of thrombotic events in ET patients. Therefore, it has been included in prognostic models and its presence may guide treatment decisions 36,37 . Subsequent meta analyses and systematic reviews of the literature showed that among patients with ET, the risk of thrombosis is about twice as high in those with the JAK2V617F mutation compared to those without.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been included in prognostic models and its presence may guide treatment decisions. 36 , 37 Subsequent meta analyses and systematic reviews of the literature showed that among patients with ET, the risk of thrombosis is about twice as high in those with the JAK2V617F mutation compared to those without. Based on this data, patients with CALR mutation have better prognosis with lower incidence of thrombotic events relative to patients bearing JAK2V617F mutation associated with an increased risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%